A novel strategy for realizing dual state fluorescence and low-temperature phosphorescence. (19th December 2018) - Lei, Yunxiang; Dai, Wenbo; Liu, Zhiqi; Guo, Shuai; Cai, Zhengxu; Shi, Jianbing; Zheng, Xiaoyan; Zhi, Junge; Tong, Bin; Dong, Yuping
Abstract : We demonstrate a new strategy for the development of dual-state emissive materials with a positive response to temperature and long lifetime phosphorescence at low temperature. Abstract : We demonstrate a new strategy for the development of dual-state emissive materials by introducing phenyl groups to triphenylpyrrole (TPP) isomers. The phenyl group can increase the rotational barrier and restrict the intramolecular rotation of TPP, thus enhancing the fluorescence efficiency of aggregation induced emission (AIE) materials in solution. Fluorescence of TPP derivatives was not quenched by the drastic intermolecular collision and intramolecular motion at high temperature. On the contrary, the fluorescence of their solutions showed a positive response to temperature. Theoretical calculations demonstrated that the molecules exhibited a higher planar conformation at high temperature. Three donor–acceptor samples with a twisted intramolecular charge transfer (TICT) effect showed a strong phosphorescence with a lifetime up to 10 s at low temperature.